2024
DOI: 10.1186/s12964-023-01388-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages reprogramming driven by cancer-associated fibroblasts under FOLFIRINOX treatment correlates with shorter survival in pancreatic cancer

Zainab Hussain,
Thomas Bertran,
Pascal Finetti
et al.

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) remains a clinically challenging cancer, mainly due to limited therapeutic options and the presence of a highly prominent tumor microenvironment (TME), facilitating tumor progression. The TME is predominated by heterogeneous populations of cancer-associated fibroblasts (CAFs) and tumor associated macrophages (TAMs), in constant communication with each other and with tumor cells, influencing many tumoral abilities such as therapeutic resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…An interesting question is how do M1 macrophages and CAFs interact within the TME to promote cancer progression? Zainab and colleagues demonstrated that CAFs polarize M0 naïve and M1 macrophages towards an M2-like phenotype with a specific increase in CD200R and CD209 M2 markers [ 51 ] ( Table 3 ).…”
Section: Role Of Monocytes/macrophages In Cancer Progression and Meta...mentioning
confidence: 99%
See 3 more Smart Citations
“…An interesting question is how do M1 macrophages and CAFs interact within the TME to promote cancer progression? Zainab and colleagues demonstrated that CAFs polarize M0 naïve and M1 macrophages towards an M2-like phenotype with a specific increase in CD200R and CD209 M2 markers [ 51 ] ( Table 3 ).…”
Section: Role Of Monocytes/macrophages In Cancer Progression and Meta...mentioning
confidence: 99%
“…Naturally, the crosstalk between CAFs and macrophages occurs through the production of specific cytokines and chemokines such as CXCL13, CCL26, CXCL1, IL-1β, IL-21, IL-23, CCL3, MMP-1, RANKL, TNF-α, VEGF-D, CCL7, and SDF-1α [ 51 ].…”
Section: Role Of Monocytes/macrophages In Cancer Progression and Meta...mentioning
confidence: 99%
See 2 more Smart Citations